Nasal Cytology in Eosinophilic Granulomatosis with Polyangiitis - David Longhino; Arianna Aruanno; Eleonora Nucera (Sinusitis)
In recent years, nasal cytology (NC) has become a valuable diagnostic tool in rhinology due to its easy practicability, non-invasiveness, and low cost [...]